Rules and validation processes for interoperable BIM data exchange. Issue 1 (27th August 2020) - Lee, Yong-Cheol; Eastman, Charles M; Solihin, Wawan
Abstract: Diverse industries have recognized the significance of a neutral data standard for seamless building information modeling (BIM) data exchanges and adopted commonly agreed schemes such as the industry foundation classes (IFC) schema for enhancing BIM data interoperability. To selectively employ domain-specific data exchange requirements, the AEC-FM (the Architecture, Engineering, Construction, and Facility Management) industries have developed their own schema with a subset of the IFC schema, named a model view definition (MVD). However, because of latent human errors, inadequate MVD definitions, and error-prone data mapping problems, the adoption of IFC for exchanging and sharing BIM data is frequently limited with severe data integrity issues. This challenging situation requires the detailed examination of the limitations of the heterogeneous IFC translation processes of the current BIM authoring and application tools. To accomplish this objective, the authors thoroughly investigated the two MVDs, the Coordination View Version 2.0 and the Construction Operations Building Information Exchange, broadly used as an international standard for developing the IFC translation processes, and then identified their intrinsic requirements/rules and developed rule-based data validation processes. These new intrinsic knowledge of the two MVD specifications will be fundamental foundations to create coherent BIM data exchange systems that are currently scattered and dispersed in heterogeneous IFC translation processes and structures. Newly revealed rules pertaining to these two MVDs have been executed with IfcDoc, which is the IFC documentation tool. This BIM data validation process is expected to not only accurately evaluate the translation processes between BIM native data and IFC ones but also help industry professionals ensure the integrity and the accuracy of their BIM data according to the BIM data exchange standards using the two MVDs. In addition, the outcomes of this research study are expected to bolster the interoperable BIM adoption and offer the values of greater consistency of BIM data exchange. Graphical Abstract: